Implementasi Routing Statis menggunakan Media Komunikasi LoRa dan Websocket untuk Pengiriman Data dari Sensor ke Cloud pada IoT - Mohamad Lutfi; Primantara Hari Trisnawan; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
In general, the IoT environment consists of the internet and the Wireless Sensor Network (WSN). WSN is a collection of sensor nodes that can collect data and communicate with each other. To communicate with each other, WSN requires a protocol, for example is LoRa. LoRa has the advantages of wide coverage and low power consumption. However, LoRa has a weakness. The communication is still limited to one hop and LoRa cannot directly send data to the cloud. To solve the one-hop problem, static routing is used, so that it can send data in multi-hop. Static routing is used because it is suitable for small network implementations. For the problem of not being able to send data to the cloud, a gateway that can communicate with the cloud is added using the Websocket protocol. Websocket was chosen because it has a smaller round trip time than MQTT and lighter than HTTP. Performance testing is carried out with three parameters, successful rate, round trip time and delay. The results of the successful rate test, data from nodes 1 and 2 are sent and stored 100% to the cloud, node 3 is sent 94%,, while sensor node 4 is sent 92%. The results of the round trip time test are that nodes 1 and 2 require 0.2 seconds, node 3 takes 0.4 seconds and node 4 takes 0.7 seconds The more hops that are passed, the more risk of data loss and resulting the longer time The results of the delay test, in the first experiment the sensor node 2 got the longest results and in the second test it got the fastest results. This is influenced by internet network conditions which make different results.